Kajian dan Perancangan Mebel Fleksibel pada Retail Sepatu dan Tas Bergaya Modern - Wagiri, Felicia; Santosa, Adi; suprobo, filipus priyo (Intra, 2014)
Nowadays, store-based retailing is one of the most popular businesses. Fierce competition requires retailers to be able to accommodate customer’s needs with high integrity and competitive interior design at the modest price. Design shall be flexible and adaptive to the changes. Therefore, it is essential to make a furniture design which enhances the efficiency and effectiveness value that leads to the convenience of the users. It would be only achieved by conducting a thorough survey as well as a comprehensive study literature of the layout basics, furniture design types and terms, construction systems, and alternatives studies of styles and materials selection. Thus the formula will be obtained in the form of provisions in the good design of a flexible furniture, that will be applied in the design for shoes and bags retail.